"Be not deceived" : the sacred and sexual struggles of gay and ex-gay Christian men - Wolkomir, Michelle, 1966- (Rutgers University Press, 2006)
Homosexuality has become increasingly accepted in mainstream America over the past two decades. Yet despite indications of progress that can be found everywhere from academia to popular culture, gay men and women remain the target of much discrimination and stigma, particularly within conservative Christianity. In "Be Not Deceived", Michelle Wolkomir explores the difficult dilemma that gay Christians face in their attempts to reconcile their religious and sexual identities. She introduces the ideologies and practices of two alternative, and competing, ministries that offer solutions for Christians who experience homosexual desire. Using ethnographic data, she examines the implications of these ministries for the men who participate in them, for their families, and for understanding contemporary debates surrounding homosexuality in American society. One organization - the Universal Fellowship of Metropolitan Community Churches - believes that God made people gay to suit divine purposes. Changing one's sexuality is therefore impossible and a defiance of God.; In contrast, Exodus International preaches that homosexuality is a sin and a symptom of disordered psychological development - one that can be cured through redemptive prayer. By comparing participant experiences in these ministries, Wolkomir explores the paths and processes by which members learn to become gay or ex-gay Christians. Through careful analysis of the groups' ideologies, interactions, and symbolic resources, "Be Not Deceived" goes far beyond the obvious differences between the ministries to uncover their similarities, namely that both continue to define heterosexuality as the normative and dominant lifestyle
Keywords: Christian gay men -- Religious life.; Christian gay men -- Sexual behavior.; Religion.; Philosophy & Religion.; Christianity.; Homosexuels masculins chrétiens -- Vie religieuse.; Homosexuels masculins chrétiens -- Sexualité.; RELIGION -- Christianity -- General.; RELIGION -- Christian Life -- Social Issues.; Christian gay men -- Religious life; Electronic books.